Rattus blangorum Miller 1942 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus blangorum Miller 1942 Rattus blangorum Miller 1942, Proc. Acad. Nat. Sci. Philadelphia, 94: 145. Type Locality: Indonesia, N Sumatra, Aceh foothills of Gunung Leuser, near Blangnanga Base Camp, 3600 ft (1097 m; see Miller, 1942, for details). Vernacular Names: Aceh Rat. Distribution: Known only from the type locality. Discussion: Rattus rattus species group. Still represented only by the holotype and another specimen (ANSP 20348, 20349). Originally described as a species (Miller, 1942), but later included in R. tiomanicus (Musser and Califia, 1982; Corbet and Hill, 1992; Musser and Carleton, 1993). Recent multivariate analyses employing morphometric traits of Sundaic samples of the R. tiomanicus complex indicate blangorum to be distinct from all other insular samples in that assemblage, which is partly a reflection of its small body size compared to the usual size range in R. tiomanicus (Musser, ms.). Member of the suite of murine species endemic to Sumatra (Musser, 1986, and account of Maxomys hylomyoides ). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Muridae, pp. 1189-1531 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 1467, DOI: 10.5281/zenodo.7316535